A Case of Orbital Emphysema Associated with Frontal Sinus Pneumocele - Sasaki, Takahiro; Yamoto, Toshikazu; Fujita, Koji; Nakao, Naoyuki (Journal of Neurological Surgery Reports, 2013)
Orbital emphysema is usually caused by trauma and fracture of an orbital bone, allowing air to pass from the sinuses into the orbit. Orbital emphysema without any significant trauma is rare. We present a case of a 67-year-old-woman who complained of left exophthalmos without any history of trauma, sneezing, or sinus surgery. Computed tomography scanning showed left orbital emphysema protruding the eyeball forward. The left frontal sinus was remarkably enlarged associated with a partial defect of the orbital roof, allowing air entry into the orbit. In addition, the frontal sinus ostium was occluded with the mucocele that served as a one-way valve between the frontal and the ethmoidal sinuses. We performed frontal craniotomy and removed the mucocele and the inner table of frontal bone to communicate the frontal sinus with the nasal cavity. After operation, her exophthalmos was improved.
Keywords: orbital emphysema; frontal sinus pneumocele; transcranial surgery